Antioxidant properties of Psidium guajava leaf extract on paraquat induced hepatotoxicity and oxidative stress - Okorondu, M. M.; Okorondu., S. I. (African Science Publications, 2021)
Thirty healthy male rats were used for the in vivo experiment. Animals received 3.5 mg/kg of Paraquat (PQ) intraperitoneally on the 15th day of experiment. Extracts were administered daily for thirty (30) days using normal saline. Liver parameters were analyzed to assess hepatoprotection. Malondialdehyde concentration was estimated to assess peroxidation. Glutathione (GSH) concentration was estimated to assess non-enzymatic antioxidant status. Activities of antioxidant enzymes were further used to assess antioxidant capacity of Psidium guajava (PG) against PQ-induced oxidative damage. Hematological indices were evaluated to assess the effect of PG on haemopoesis. Histological study of the liver was also carried out to find out the level of effectiveness of PG. The antimicrobial activity of the extract was also determined. Results showed that there was a significant increase in ALT and AST activities, albumin/globulin ratio, malondiadehyde (MDA), following PQ exposure at (p < 0.05). There was also a significant decrease of total protein and globulin concentrations, Packed Cell Volume (PCV), Red Blood Cell (RBC) count, Superoxide Dismutase (SOD), and GSH after PQ exposure at (p < 0.05). The histological result showed that PG leaf extract significantly improved changes in oxidative stress parameters, blood parameters, and hepatotoxicity induced by PQ administration at p < 0.05. Thus, PG leaf ethanol extract may be recommended in hepatotoxicity.
Keywords: Antioxidant, Hepatotoxicity, Oxidative stress, Paraquat, Psidium guajava